TINGKAT LAYANAN INTERVENSI DALAM PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS TERINTEGRASI - Anggraini, Era; Wandira, Ayu; Andriani, Opi; Novalia, Ratih Juwita (Program Studi Pendidikan Vokasi Seni Kuliner, 2023)
Education is a conscious effort to prepare students through learning activities, guidance and practice to achieve knowledge that will be useful in the future. This research aims to determine the level of intervention services in the education of children with special needs. Intervention is an activity to stimulate children's basic abilities carried out on children who are slow or who have risk factors with the aim of catching up so that the deviations that occur do not get worse, or so that the obstacles that occur do not have a negative impact on subsequent development. This research uses a qualitative approach with in-depth research and observation as data collection methods. This research was conducted on students with certain disabilities in Bungo Regency by involving children with special needs in Bungo Regency. The level of intervention services carried out and followed up is in accordance with the limitations of the child with special needs.